1983
DOI: 10.1161/01.hyp.5.2_pt_2.i70
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and reflex responses to acute and chronic antihypertensive therapy with the calcium entry blocker nifedipine.

Abstract: SUMMARY Calcium entry blockers are potent vasodilators and may be suitable for antihypertensive therapy. We investigated hemodynamic responses together with changes of plasma catecholamines and renin activity (PRA) in 11 men (38.2 ± 5 . 1 years) with essential hypertension (EHT, WHO I-II) after administration of nifedipine 10 mg sublingually (s.l.) and after 6 weeks treatment with nifedipine 20 mg three times daily. Acutely, nifedipine 10 mg s.l. decreased intraarterial blood pressure (BP, 156.2 ± 5.3/83.1 ± 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
2

Year Published

1983
1983
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(50 citation statements)
references
References 36 publications
3
45
2
Order By: Relevance
“…The finding that with the intravenous infusions the increase in flow was almost exclusively confined to the subepicardial layers is not surprising in view of the tachycardia and hypotension (Domenech & Goich, 1976); this has also been demonstrated for nicorandil (Verdouw et al, 1987). Chronic treatment often leads to a reduction of the reflex tachycardia (Kiowski et al, 1983). If the coronary vasodilator action were to be sustained with chronic treatment, the lower heart rate would most likely not only lower myocardial 02-demand but also shift coronary blood flow in favour of the subendocardial layers.…”
Section: Discussionmentioning
confidence: 88%
“…The finding that with the intravenous infusions the increase in flow was almost exclusively confined to the subepicardial layers is not surprising in view of the tachycardia and hypotension (Domenech & Goich, 1976); this has also been demonstrated for nicorandil (Verdouw et al, 1987). Chronic treatment often leads to a reduction of the reflex tachycardia (Kiowski et al, 1983). If the coronary vasodilator action were to be sustained with chronic treatment, the lower heart rate would most likely not only lower myocardial 02-demand but also shift coronary blood flow in favour of the subendocardial layers.…”
Section: Discussionmentioning
confidence: 88%
“…The literature is conflicting on the question of persisting sympathetic hyperactivity following calcium antagonism, but the majority of reports suggest that hyperactivity does persist even with the long acting preparations. 5,9,[18][19][20][21] Recently, it has been shown that peripheral muscle sympathetic activity as recorded by microneurography was increased over baseline after 4 weeks treatment with amlodipine. 21 It has been suggested that one reason for the persisting sympathetic activity with short acting calcium antagonists relates to the profile of induced blood pressure reduction with formulations which cause rapid falls in blood pressure and doses or dosing intervals which result in substantial peak:trough ratios, thus causing increases in sympathetic activity in the initial hours after dosage.…”
Section: Figurementioning
confidence: 99%
“…This indirect method is based on the assumption that the drugs under study do not alter the hepatic extraction ratio of ICG and in the case of glyceryl trinitrate there is no evidence that this occurs in cirrhotic patients (Groszmann et al, 1982). Studies were performed in random order and separated by at least 3 days, as control, 5 min following glyceryl trinitrate (500 ,ug sublingually) and 30 min following nifedipine (10 mg sublingually) at which time these drugs produce their maximum effects (Maclean & Feely, 1983;Kiowski et al, 1983 Figure 1 Effect of glyceryl trinitrate (500 ,ug) and nifedipine (10 mg) on apparent liver blood flow in six subjects.…”
Section: Introductionmentioning
confidence: 99%